(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Ambedkar launched a single-handed attack on caste- system at a time where it was most needed. It was indeed a praiseworthy step. However, it would have been better, perhaps, to direct this attack against the system rather than against the individuals. Whatever he thought about Mahatma Gandhi (much is not known about it), his views on the ancient law-giver, Manu, and his famous ‘Manusmriti’ are well known. Ambedkar himself knew quite well that Manu was not the inventor of the Caste system he merely codified the already existing rules of conduct. Manu’s advocacy of “Chatur-Varna” was not the result of his individual thinking on the continuation of the Caste-System he was only trying to systemize what was scattered in the Shastras and the Puranas. During the Mohad Tank Satyagraha, launched under the leadership of Ambedkar, a copy of the ‘Manusmriti’ was burnt, and Ambedkar approved of this act.One may not approve Ambedkar’s sociological ideas regarding the birth of the Caste system and may not like the idea of the “Manu Smriti” being burnt, but Ambedkar’s deep concern for the depressed classes and his intense desire to work for their regeneration was, however, absolutely genuine. He was against the idea codified in the “Manusmriti” because these idea support the Caste system and regard the people of the depressed classes as the Untouchables. How can one be an Untouchable or depressed classes as the Untouchables. How can one be an Untouchable if one is a human being? All human beings are alike, made of the same clay, subject to the same emotions and feelings. How can, then, one class of human beings, be treated as inferior to the other?